HEALTH ORIENTED PEDAGOGICAL THINKING IN HIGHER EDUCATION AS A FOUNDATION FOR STUDENT WELLBEING AND SUSTAINABLE DEVELOPMENT - Ernazarov Abduvali Beknazarovich (Innovate Conferences, 2025)
This article explores the development of health-oriented pedagogical thinking among students in higher education as a foundational aspect of comprehensive personality development. In light of today’s complex socio-ecological and technological challenges, fostering a mindset that prioritizes health is increasingly vital. The paper emphasizes the central role of educators in modeling and promoting healthy lifestyles, alongside the strategic use of pedagogical methods such as problem-based learning, role-play, and reflective practices. It also highlights the importance of digital technologies and institutional environments in shaping sustainable habits, personal responsibility, and well-being. The article advocates for a culturally sensitive, ethically grounded, and student-centered approach, arguing that health-oriented pedagogy contributes not only to individual development but also to national and global health objectives, including the UN Sustainable Development Goals. Ultimately, it positions health-oriented thinking as a transformative force that bridges academic learning and personal growth, preparing students for responsible, resilient, and socially engaged lives.
Keywords: Health-oriented thinking, higher education, pedagogical strategies, student well-being, digital health tools, reflective learning, inclusive pedagogy, sustainable development, educator influence, health education, psychological resilience, educational innovation.